Effectiveness of an Immersive Virtual Environment (CAVE) for teaching pedestrian crossing to children with PDD-NOS - Tzanavari, Aimilia; Charalambous-Darden, Nefi; Herakleous, Kyriakos; Poullis, Charalambos (My University, 2015)
Children with Autism Spectrum Disorders (ASD) exhibit a range of developmental disabilities, with mild to severe effects in social interaction and communication. Children with PDD-NOS, Autism and co-existing conditions are facing enormous challenges in their lives, dealing with their difficulties in sensory perception, repetitive behaviors and interests. These challenges result in them being less independent or not independent at all. Part of becoming independent involves being able to function in real world settings, settings that are not controlled. Pedestrian crossings fall under this category: as children (and later as adults) they have to learn to cross roads safely. In this paper, we report on a study we carried out with 6 children with PDD-NOS over a period of four (4) days using a VR CAVE virtual environment to teach them how to safely cross at a pedestrian crossing. Results indicated that most children were able to achieve the desired goal of learning the task, which was verified in the end of the 4-day period by having them cross a real pedestrian crossing (albeit with their parent/educator discretely next to them for safety reasons).
Keywords: ASD; Autism; CAVE; Children; Learning; PDD-NOS; Pedestrian crossing